APLIKASI SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH-WEB) DI KUA KECAMATAN CIBEUREUM KOTA TASIKMALAYA - Yanti Haryanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) – Sekolah Tinggi Agama Islam (STAI) Pelita Nusa Bandung Barat, 2024)
This research is motivated by the application of the Marriage Management Information System (SIMKAH) application, a program from the Ministry of Religion of the Republic of Indonesia designed to facilitate the presentation of marriage data at the Office of Religious Affairs (KUA). This study aims to describe the application of SIMKAH in administrative services in the Cibeureum District KUA and evaluate its effectiveness. The research method used is field research with a qualitative approach, which aims to reveal ongoing phenomena. The researcher made direct observations at the KUA of Cibeureum District, Tasikmalaya City. The results of the study show that SIMKAH has been implemented in accordance with regulations, which can be seen from the recording of organized marriage data. However, there are obstacles in online marriage registration, including errors in entering marriage location data, which should be outside the office but recorded in the office, thus hindering the issuance of payment billing. To overcome this obstacle, KUA officers through religious extension officers conducted socialization related to marriage registration procedures at SIMKAH. In conclusion, the implementation of SIMKAH has increased the efficiency of marriage data collection in the KUA of Cibeureum District, although there are still obstacles in the implementation of online registration in the field.